HUBUNGAN PRESTASI BELAJAR PENDIDIKAN ISLAM DAN AKHLAK PESERTA DIDIK DI SMP MA’ARIF BATU - Miftah Ika Fadhilah Putri; Illyas Thohari; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Learning achievement is the result obtained by students in the learning process that can change something that exists in students. Good learning achievements, must also be balanced with good morals, so accepting students have good learning achievements, the morals of students must be good too. Morals represent daily behavior that is reflected through behavior, attitudes, and speech. Every Muslim must have good morals because there is no religion that should not be proven with morality. To find out the relationship between Islamic religious education learning achievement in Ma'arif Batu Middle School, researchers used quantitative research. To get data about the relationship between Islamic religious education learning achievement in Ma'arif Batu Middle School researchers used a questionnaire and documentation method. The results can be obtained from this study after using calculations with predictable products when related to learning outcomes with learners morals but there is a weak relationship because the results obtained are based on weak coefficient values.